Teacher's Perception of the Synectic Model and Problem-Based Learning on Poetry Writing Skills in Class IV Elementary School - Naila Nur Niswatul Ula; Panca Dewi Purwanti; Tri Agung Prasetya; Woro Sumarni; Putut Marwoto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Indonesian language lessons are often underestimated as difficult, but in reality, many students do not understand Indonesian language learning, one of which is writing poetry. Writing poetry cannot be done through conventional methods because writing poetry requires a very high imagination. One of the innovations that can be done in poetry writing is the synectic model and the problem-based learning model. The purpose of this research is an exploratory study of synectic models and problem-based learning on poetry writing skills for class IV. The method used in this research is an exploratory qualitative conducted in elementary schools in the Kanjengan Cluster, Central Semarang. The results of the analysis show that teachers need innovation in learning to increase students' imagination which will later be poured into the form of poetry. One of the innovations that can be applied is to use synectic models and problem-based learning in the process of learning to write poetry.